2017
DOI: 10.1161/jaha.117.006778
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Dendritic Cell–Mediated Activation of T Cells From Atherosclerotic Plaques by Human Heat Shock Protein 60

Abstract: BackgroundAtherosclerosis is characterized by the presence of activated immune‐competent cells including dendritic cells (DCs) and T cells, dead cells, and oxidized low‐density lipoprotein. HSP60 (Heat shock protein 60) has been implicated in atherosclerosis. A plasma protein, Annexin A5, has atheroprotective properties.Methods and ResultsHuman DCs differentiated from peripheral blood monocytes were treated with human HSP60 or HSP90 and autologous T cells were cocultured with these pretreated DCs (mDCs). HSP60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 40 publications
0
32
0
1
Order By: Relevance
“…The reasons to focus on Hsp60 as biomarker useful in patient management and as a potential pathogenic agent in IBD are varied, as follows: (1) Hsp60 can induce production of pro-inflammatory cytokines (Sangiorgi et al, 2017; Cheong et al, 2018; Sun et al, 2018; Swaroop et al, 2018); (2) its quantities in UC mucosa vary in parallel with disease status, high in relapse and low in remission (Rodolico et al, 2010; Tomasello et al, 2011b); (3) its reported role in other conditions with inflammatory component, for instance atherosclerosis (Grundtman et al, 2011; Wick et al, 2014; Wick, 2016; Rahman et al, 2017); (4) there is ample epitope sharing between Hsp60s of various origins and human Hsp60 and other tissues (including intestinal ones). This molecular mimicry (Bachmaier and Penninger, 2005) elicits crossreactive antibodies reacting not-only with the immunizing antigen (e.g., Hsp60 from a bacterium infecting the intestinal or the genitourinary tract), but also with human Hsp60 and intestinal antigens (Füst et al, 2012).…”
Section: The Bowel and Its Inflammatory Diseases: A Brief Overviewmentioning
confidence: 99%
“…The reasons to focus on Hsp60 as biomarker useful in patient management and as a potential pathogenic agent in IBD are varied, as follows: (1) Hsp60 can induce production of pro-inflammatory cytokines (Sangiorgi et al, 2017; Cheong et al, 2018; Sun et al, 2018; Swaroop et al, 2018); (2) its quantities in UC mucosa vary in parallel with disease status, high in relapse and low in remission (Rodolico et al, 2010; Tomasello et al, 2011b); (3) its reported role in other conditions with inflammatory component, for instance atherosclerosis (Grundtman et al, 2011; Wick et al, 2014; Wick, 2016; Rahman et al, 2017); (4) there is ample epitope sharing between Hsp60s of various origins and human Hsp60 and other tissues (including intestinal ones). This molecular mimicry (Bachmaier and Penninger, 2005) elicits crossreactive antibodies reacting not-only with the immunizing antigen (e.g., Hsp60 from a bacterium infecting the intestinal or the genitourinary tract), but also with human Hsp60 and intestinal antigens (Füst et al, 2012).…”
Section: The Bowel and Its Inflammatory Diseases: A Brief Overviewmentioning
confidence: 99%
“…In our studies, we focused on stability and structure of the HSP60 with MTS, which we designate naïve HSP60, as it occurs after being synthesized in the cytosol and before entering the mitochondria (Vilasi et al, 2014 ). These studies were stimulated by the increased awareness of the potential roles of Hsp60 in cell compartments other than mitochondria and outside the organelle (Soltys and Gupta, 1998 ; Cechetto et al, 2000 ; Cappello et al, 2008 , 2014 ; Wick et al, 2014 ; Wick, 2016 ; Rahman et al, 2017 ; van Eden et al, 2017 ; Calderwood, 2018 ; Pockley and Henderson, 2018 ; see other references at http://hsp60.com/localization/ ). By Electron Microscopy, it has been demonstrated that in normal conditions, 15–20% of Hsp60 is located at extra-mitochondrial sites, namely, in the mitochondrial outer membrane, cytosolic vesicles plasma membrane, endoplasmic reticulum, and peroxisomes (Soltys and Gupta, 1998 ).…”
Section: Hsp60 Outside Mitochondriamentioning
confidence: 99%
“…Hsp60 is also involved in assembly of membrane proteins and in the condensation of urate oxidase crystalline core of rat liver peroxisomes. It is especially in pathologic situations such as cancer and autoimmune and inflammatory diseases that HSP60 accumulates in the cytosol, and in extramitochondrial sites (Czarnecka et al, 2006 ; Desmetz et al, 2008 ; Cappello et al, 2011 , 2014 ; Macario et al, 2013 ; Wick et al, 2014 ; Macario and Conway de Macario, 2016 ; Rahman et al, 2017 ; van Eden et al, 2017 ; Calderwood, 2018 ; Pockley and Henderson, 2018 ). The question still open is how the protein reaches these sites, and, consequentially, which forms of Hsp60 can be found in the various locations.…”
Section: Hsp60 Outside Mitochondriamentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo AnxA5 dampens inflammation when administered to various mouse models [ 9 11 ]. Recent evidence also points to AnxA5 as a modulator of T-cell activation by reducing LDL mediated expression of the Human Heat Shock Protein 60 (HSP-60) [ 12 ].…”
Section: Introductionmentioning
confidence: 99%